From Perception to Decision: The Role of Marketing Mix, Service Quality, and Consumer Trust in Medical On-Call Services - Susanto, Dede Himawan Dwi; Hidayat, Dasrun; Widjaja, Yani Restiani (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study examines the influence of marketing strategy, service quality, and consumer trust on the decision to use medical on-call services, with consumer perception positioned as a mediating variable. Employing an explanatory sequential mixed methods design, the quantitative phase involved 95 users surveyed through a Likert-scale questionnaire and analyzed using multiple linear regression and mediation testing. The qualitative phase consisted of in-depth interviews with five informants to contextualize statistical findings and explore users’ evaluative mechanisms. The results show that marketing strategy and service quality have a positive and significant effect on service-use decisions, whereas trust does not exert a direct influence. Consumer perception emerged as the only variable with a strong direct effect on decision-making and mediates the effects of marketing strategy and service quality partially, while fully mediating the effect of trust. Qualitative themes reinforce these findings by revealing that users’ decisions are shaped by clarity of information, responsiveness, medical competence, perceived safety, and the relevance of services to personal needs. The study concludes that perception functions as the core cognitive–affective mechanism linking external stimuli to behavioral decisions in digital healthcare services. Managerial implications highlight the importance of perception-based service design, consistent communication, data security, and improved clinical interaction quality.